Gambaran dan Anatomi Ginjal Sapi Sumba Ongole (Bos indicus) - Claudia Beatrice; Filphin A Amalo; Inggrid T Maha; Heny Nitbani (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Sumba Ongole Cattle (Bos indicus) is one of the local breed cattle in Indonesia and is properly developing on the island of Sumba. One of the organ systems that has important role in cleanig the rest of metabolism in animals are kidney. This research is aimed to observe the structure of anatomy and histologycal of the kidney. This study uses 3 pairs of kidney of the male and female sumba ongole cattle with age range 3-5 years. Samples are colected in Rumah Potong Hewan (RPH) Regency of East Sumba. Macroscopic observations were performed, and sample were fixed in 10% formalin solution. Furthermore, on the histological preparations and continued with HE staining. The macroscopic of the kidney showed that sumba ongole cattle had lobed shape, elastic consistency, adn brownish red in color. Meanwhile in microscopic observations showed, there are glomerulus, Bowman’s capsule, urin space/ Bowman’s space, mesangial cell, macula densa, proximal convolated tubule, distal convulated tubule, and collecting tubule.